The life and death of Adolf Hitler - Giblin, James Cross (Clarion Books, 2002)
Explores the life of the dangerous and destructive dictator Adolf Hitler whose aggressive foreign policies set off World War II and caused the deaths of over 6 million Jews. He committed heinous crimes against humanity worldwide.